Qualitative research is about listening and growing - Warren Bareiss (Qualitative Research in Medicine & Healthcare, 2025)
Change can be frightening. Or maybe it’s better to say that the thought of change can be frightening. Qualitative Research in Medicine & Healthcare is about to see a major change as it shifts publishers from PAGEPress to KeAi Publishing. This will be the last issue published by PagePress, where it began in 2017 under the leadership of founding editor, Mariaelena Bartesaghi. I became editor in 2021.